Starch Synthase 4 and Plastidal Phosphorylase Differentially Affect Starch Granule Number and Morphology. Issue 1 (8th March 2017) - Malinova, Irina; Alseekh, Saleh; Feil, Regina; Fernie, Alisdair R.; Baumann, Otto; Schöttler, Mark Aurel; Lunn, John E.; Fettke, Joerg
Abstract : PHS1 and SS4 are differently involved in regulating starch granule generation and the formation of spherical starch granules, although SS4 exerts stronger influence. Abstract: The process of starch granule formation in leaves of Arabidopsis ( Arabidopsis thaliana ) is obscure. Besides STARCH SYNTHASE4 (SS4), the PLASTIDIAL PHOSPHORYLASE (PHS1) also seems to be involved, since dpe2-1/phs1a double mutants lacking both PHS1 and the cytosolic DISPROPORTIONATING ENZYME2 (DPE2) displayed only one starch granule per chloroplast under normal growth conditions. For further studies, a dpe2-1/phs1a/ss4 triple mutant and various combinations of double mutants were generated and metabolically analyzed with a focus on starch metabolism. The dpe2-1/phs1a/ss4 mutant revealed a massive starch excess phenotype. Furthermore, these plants grown under 12 h of light/12 h of dark harbored a single large and spherical starch granule per plastid. The number of starch granules was constant when the light/dark regime was altered, but this was not observed in the parental lines. With regard to growth, photosynthetic parameters, and metabolic analyses, the triple mutant additionally displayed alterations in comparison with ss4 and dpe2-1/phs1a . The results clearly illustrate that PHS1 and SS4 are differently involved in starch granule formation and do not act in series. However, SS4 appears to exert a stronger influence. In connection with the characterized double mutants, we discuss the generation of starch granules and the observed formation of spherical starch granules.